Bioactive Lipids-Based Approach to Aging Associated Diseases/Disorders. (29th May 2020) - Das, Undurti
Abstract: Objectives: To investigate the role of bioactive lipids (BAL) in ageing associated disorders such as obesity, type 2 diabetes mellitus, hypertension, coronary heart disease, immune dysfunction and cancer. Methods: We recruited known patients of type 2 diabetes mellitus, hypertension, coronary heart disease, diabetic nephropathy and cancer and collected their blood samples for the study. In these samples the concentrations of various BAL such as linoleic acid, gamma-linolenic acid, dihomo-gamma-linolenic acid, arachidonic acid, alpha-linolenic acid, eicosapentaenoic acid, docosahexaenoic acid and other lipids in their phospholipid fraction was measured. The role of these BAL in these diseases was also studied in animal models of diabetes mellitus and cancer. To evaluate the mechanism of action of BAL, in animal models of type 2 diabetes mellitus and cancer, the expression of NF-kB, IKB, COX-1, COX-2 and LOX and plasma levels of IL-6, TNF, nitric oxide and lipid peroxides was also studied. Results: Plasma levels of arachidonic acid in the phospholipid fraction was found to be low in all the patients recruited in the study. In some of these patients plasma levels of gamma-linolenic acid, eicosapentaenic acid and docosahexaenoic acid were also found to be altered. But, of all the lipids estimated, arachidonic acid was found to be consistently low in those with obesity, type 2 diabetes mellitus, hypertension, coronary heart disease and cancer. In animal models of type 2 diabetes mellitus, hypertension and cancer, administration of arachidonic acid produced significant amelioration of these conditions suggesting a critical role for this lipid in these diseases. Further studies revealed that arachidonic acid suppresses inflammation and enhanced the formation of lipoxin A4 (LXA4), which is a potent anti-inflammatory compound. A significant suppression of pro-inflammatory genes and restoration of anti-oxidant status to normal. Conclusions: Based on the results of the present study, ageing associated diseases such as obesity, type 2 diabetes mellitus, hypertension, coronary heart disease, and cancer are inflammatory conditions with low circulating concentrations of arachidonic acid and lipoxin A4. These results imply that appropriate administration of arachidonic acid and lipoxin A4 could be of benefit in ageing and ageing associated diseases. Funding Sources: Nil.